#TITLE_ALTERNATIVE# - AULIA AKBAR (NIM : 10106046); Dosen Pembimbing : Dr. L.H. Wiryanto, ADIL
A free surface flow on a terminated channel. This flow is uniform in far upstream and formed waterfall at the end of channel. This flow is supercritical. Flow's rate is described by Froude number F. An integral equation is used to modeled the flow. This integral equation is formulated from governing equation by defining hodograph variable, corresponding to particle velocity along a stream line. Then, a system of non-linear equation is constructed from the integral equation. This system of equation is solved numerically to obtain profile of the flow. Numerical simulation can explained effect of flow's rate to waterfall shaped.